2022
DOI: 10.3390/vetsci9050207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graded Levels of Fenugreek (Trigonella foenum-graecum L.) Seeds on the Growth Performance, Hematological Parameters, and Intestinal Histomorphology of Broiler Chickens

Abstract: Two experiments were conducted to evaluate the effects of fenugreek seeds (FS) as a potential alternative to antibiotic growth promoters in broiler chickens. In the first experiment, one-day-old Ross (n = 160) straight-run broilers were fed FS at 0 g, 2.5 g, 5 g, and 10 g/kg of diet during the starter (from 1 to 21 days) and finisher phase (from 22 to 35 days) with four replicates of ten birds each. In the second experiment, one-day-old Ross (n = 144) male broilers were fed 0 g, 5 g, and 10 g FS per kilogram o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…As compared with T1, similar result was recently reported by Paneru et al [45] who found that was no changing in PCV value, H/L counts in broiler chickens at 6 weeks fed diet containing 5 g/kg FSP.…”
Section: Discussionsupporting
confidence: 88%
“…As compared with T1, similar result was recently reported by Paneru et al [45] who found that was no changing in PCV value, H/L counts in broiler chickens at 6 weeks fed diet containing 5 g/kg FSP.…”
Section: Discussionsupporting
confidence: 88%
“…The research by Paneru et al (2022) demonstrates that fenugreek seed supplementation in broiler chickens had negative effects on early growth performance, haematological parameters and intestinal morphology. In turn, the results of the Paredes López et al (2018) study shows that Creole laying hens, reared in an extensive system, exhibited distinct blood biochemical profiles and higher levels of albumin, triglycerides and cholesterol compared to Hy‐Line Brown hens.…”
Section: Resultsmentioning
confidence: 99%
“…This study employed previously described methods for animal husbandry, diet formulation, and the experimental design [ 24 ]. Briefly, one-day-old, male broiler chicks (Ross 708, Hot Springs, AR, USA, n = 144) were randomly allocated into 18 floor pens with fresh pine wood shavings.…”
Section: Methodsmentioning
confidence: 99%
“…The dietary treatments consisted of three groups: a control group fed with basal diet without fenugreek seeds (CON), a basal diet with 5 g/kg fenugreek seeds (FS5), and a basal diet with 10 g/kg fenugreek seeds (FS10) during the starter (0 to 21 days) and grower–finisher (22 to 42 days) periods. The formulations for the starter and grower–finisher diets were published previously [ 24 ]. We added fenugreek seeds (Deep Foods Inc., Union City, NJ, USA) to the starter and finisher diets after grinding them to medium texture in a grinding grain mill (Thomas Scientific, Swedesboro, NJ, USA) with a 1 mm sieve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation